The Relationship Between Smartphone Addiction Levels and Sleep Quality Among University Students - Slamet Adi Setyawan; Ellia Ariesti; Monika Luhung (CV. CENDIKIA JENIUS INDONESIA, 2025)
Smartphone addiction is a condition of excessive attachment to mobile phones that can negatively affect health, including causing sleep disturbances. University students are among the groups most vulnerable to decreased sleep quality due to late-night smartphone use. This study aims to determine the relationship between the level of smartphone addiction and sleep quality among undergraduate nursing students at STIKes Panti Waluya Malang. This research used a quantitative approach with a cross-sectional design. The sample consisted of 54 respondents selected through a stratified random sampling technique conducted from May to July 2024. Data were collected using the SAS–SV questionnaire to measure smartphone addiction levels and the PSQI questionnaire to assess sleep quality. Data were analyzed using the Spearman correlation test with a 95% confidence level. The results showed a p-value of 0.212 and an r-value of 0.173, indicating no significant relationship between smartphone addiction level and sleep quality among students. In conclusion, sleep quality is not always influenced by smartphone addiction but may be affected by other factors such as stress, illness, and lifestyle. It is recommended that students manage their smartphone usage time to maintain optimal sleep quality.